2021
DOI: 10.17921/1415-6938.2020v24n5-esp.p703-708
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de uma Suspensão Oral à Base de Aceclofenaco

Abstract: O aceclofenaco é um fármaco anti-inflamatório não-esteroidal, indicado para o tratamento de diversos processos dolorosos e inflamatórios, podendo ser incorporado em diversas formulações farmacêuticas. Formas farmacêuticas líquidas, como as suspensões orais são indicadas para melhorar a adesão ao tratamento de pacientes que possuem dificuldades para deglutir. O objetivo deste trabalho foi produzir uma suspensão oral contendo aceclofenaco como princípio ativo, bem como, realizar o controle de qualidade da formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The study by Da Cruz et al [ 49 ] supports these findings, as they observed a higher number of patients affected by the Dimorphous Leprosy type (72.08%) and Lepromatous Leprosy type (22.31%). Pereira et al [ 50 ] also present similar data, where 69.91% were infected with the Dimorphous Leprosy form, followed by the Lepromatous Leprosy form (18.29%), as well as the data presented by Melo et al [ 51 ], who observed higher frequencies in the Dimorphous Leprosy and Tuberculoid Leprosy forms, totaling an average of 44.9% of cases. However, the study by Lima et al [ 52 ] showed a discrepancy with the present study, as their data had Lepromatous Leprosy as the predominant form (52.2%) in relation to Dimorphous Leprosy with 18.8%, but it agrees with the lower frequency of the Indeterminate Leprosy and Tuberculoid Leprosy clinical forms.…”
Section: Discussionsupporting
confidence: 64%
“…The study by Da Cruz et al [ 49 ] supports these findings, as they observed a higher number of patients affected by the Dimorphous Leprosy type (72.08%) and Lepromatous Leprosy type (22.31%). Pereira et al [ 50 ] also present similar data, where 69.91% were infected with the Dimorphous Leprosy form, followed by the Lepromatous Leprosy form (18.29%), as well as the data presented by Melo et al [ 51 ], who observed higher frequencies in the Dimorphous Leprosy and Tuberculoid Leprosy forms, totaling an average of 44.9% of cases. However, the study by Lima et al [ 52 ] showed a discrepancy with the present study, as their data had Lepromatous Leprosy as the predominant form (52.2%) in relation to Dimorphous Leprosy with 18.8%, but it agrees with the lower frequency of the Indeterminate Leprosy and Tuberculoid Leprosy clinical forms.…”
Section: Discussionsupporting
confidence: 64%